Lessons from the genomes of lindane‐degrading sphingomonads. Issue 5 (21st May 2019) - Nagata, Yuji; Kato, Hiromi; Ohtsubo, Yoshiyuki; Tsuda, Masataka
Summary: Bacterial strains capable of degrading man‐made xenobiotic compounds are good materials to study bacterial evolution towards new metabolic functions. Lindane (γ‐hexachlorocyclohexane, γ‐HCH, or γ‐BHC) is an especially good target compound for the purpose, because it is relatively recalcitrant but can be degraded by a limited range of bacterial strains. A comparison of the complete genome sequences of lindane‐degrading sphingomonad strains clearly demonstrated that (i) lindane‐degrading strains emerged from a number of different ancestral hosts that have recruited lin genes encoding enzymes that are able to channel lindane to central metabolites, (ii) in sphingomonads lin genes have been acquired by horizontal gene transfer mediated by different plasmids and in which IS 6100 plays a role in recruitment and distribution of genes, and (iii) IS 6100 plays a role in dynamic genome rearrangements providing genetic diversity to different strains and ability to evolve to other states. Lindane‐degrading bacteria whose genomes change so easily and quickly are also fascinating starting materials for tracing the bacterial evolution process experimentally in a relatively short time period. As the origin of the specific lin genes remains a mystery, such genes will be useful probes for exploring the cryptic 'gene pool' available to bacteria.